Population-based health promotion perspective for older driver safety: Conceptual framework to intervention plan - Sherrilene Classen (Dove Medical Press, 2008)
Sherrilene Classen1,2, Ellen DS Lopez3, Sandra Winter2, Kezia D Awadzi4, Nita Ferree5, Cynthia W Garvan61Department of Occupational Therapy, College of Public Health and Health Professions (CPHHP), University of Florida (UF), Gainesville, FL, USA; 2PhD Program in Rehabilitation Science, CPHHP, UF Gainesville, FL, USA; 3Department of Behavioral Science and Community Health, CPHHP, UF, Gainesville, FL, USA; 4Department of Health Services Research, Management, and Policy, CPHHP, UF, Gainesville, FL, USA; 5Health Science Center Libraries, UF, Gainesville, FL, USA; 6Division of Biostatistics, College of Medicine, UF, Gainesville, FL, USAAbstract: The topic of motor vehicle crashes among the elderly is dynamic and multi-faceted requiring a comprehensive and synergistic approach to intervention planning. This approach must be based on the values of a given population as well as health statistics and asserted through community, organizational and policy strategies. An integrated summary of the predictors (quantitative research), and views (qualitative research) of the older drivers and their stakeholders, does not currently exist. This study provided an explicit socio-ecological view explaining the interrelation of possible causative factors, an integrated summary of these causative factors, and empirical guidelines for developing public health interventions to promote older driver safety. Using a mixed methods approach, we were able to compare and integrate main findings from a national crash dataset with perspectives of stakeholders. We identified: 11 multi-causal factors for safe elderly driving; the importance of the environmental factors - previously underrated in the literature- interacting with behavioral and health factors; and the interrelatedness among many socio-ecological factors. For the first time, to our knowledge, we conceptualized the fundamental elements of a multi-causal health promotion plan, with measurable intermediate and long-term outcomes. After completing the detailed plan we will test the effectiveness of this intervention on multiple levels.Keywords: safe elderly driving, mixed-method approach, public health model, intervention plan, health promotion